ADvAnced PhysioTherapy in MuSculosKeletal Triage: Investigating prognostic factors, healthcare utilisation and clinical outcomes (ADAPT MSK) - a cohort study protocol. [version 2; peer review: 1 approved, 2 approved with reservations] - Louise Keating; Fiona Callan; Helen P. French; Sarah Casserley-Feeney (HRB Open Research)
Background Clinical specialist physiotherapist-led musculoskeletal triage clinics were introduced nationally in Ireland in 2011 to improve patient care and reduce waiting times for secondary care orthopaedics and rheumatology. Evidence has shown them to be effective in reducing waiting lists, however there are currently no data on longitudinal patient outcomes following attendance at these clinics. The primary aim of this prospective, cohort study is to identify predictors of clinical outcome (pain and function) at 12-months post MSK-triage appointment. Secondary aims are to describe the clinical course of patients attending MSK triage clinics and measure self-reported use of healthcare resources up to 12 months post-MSK-triage appointment. This is a prospective cohort study. Methods ADvAnced PhysioTherapy in MuSculosKeletal Triage (ADAPT MSK) will recruit a cohort of 252 adults through musculoskeletal triage clinics across five secondary care sites in Ireland. The STrengthening the Reporting of Observational studies in Epidemiology (STROBE) guidelines will be adhered to for future reporting. Adults (≥ 18 years old) attending physiotherapist-led musculoskeletal triage clinics with musculoskeletal pain, who do not require surgical or consultant-led medical care will be considered for participation in this study. Participant demographics, health literacy, healthcare utilisation, and self-report questionnaires on pain, function, musculoskeletal health status, musculoskeletal risk stratification, fear of movement, and psychological distress will be obtained at baseline, with follow-ups at three, six, and 12 months. The primary outcomes are pain intensity and function. Secondary outcomes include musculoskeletal risk stratification status, musculoskeletal health status, healthcare utilisation, and work status. Descriptive statistics will be used to profile the cohort of participants and predictors of outcome will be assessed using multivariable linear regression. Results Results will be disseminated via peer-reviewed journal publication and presentation at national and international conferences. Engagement with a public patient involvement (PPI) panel will explore dissemination strategies for public and service user engagement.